2013
DOI: 10.1530/eje-13-0515
|View full text |Cite
|
Sign up to set email alerts
|

Presentation and surgical results of incidentally discovered nonfunctioning pituitary adenomas: evidence for a better outcome independently of other patients' characteristics

Abstract: Objective: Few data are available on the surgical results in patients with incidentally discovered nonfunctioning pituitary adenoma (NFPA). We investigated the efficacy and safety of surgery in patients with incidentally discovered NFPA. Design: Retrospective analysis of prospectively recorded outcomes. Methods: From 1990 to 2011, of 804 consecutive patients undergoing surgery for NFPA, 212 cases had an incidentally discovered tumor (26.4%). Among them, 117 patients were asymptomatic, while 95 had some visual … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
26
4
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(34 citation statements)
references
References 36 publications
3
26
4
1
Order By: Relevance
“…A retrospective analysis of 142 patients who underwent surgery due to a NFPA showed that cavernous sinus invasion, lack of radiotherapy immediately after initial pituitary surgery, and positive immunostaining for hormones other than gonadotropins were risk factors for tumor recurrence (4). Moreover, postoperative recurrence rates were found to be significantly lower in patients who were asymptomatic than symptomatic at diagnosis of an incidentally detected NFPA (13). Furthermore, the risk of tumor recurrence was higher in patients with residual tumor and in those who did not receive radiotherapy (13,14).…”
Section: █ Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…A retrospective analysis of 142 patients who underwent surgery due to a NFPA showed that cavernous sinus invasion, lack of radiotherapy immediately after initial pituitary surgery, and positive immunostaining for hormones other than gonadotropins were risk factors for tumor recurrence (4). Moreover, postoperative recurrence rates were found to be significantly lower in patients who were asymptomatic than symptomatic at diagnosis of an incidentally detected NFPA (13). Furthermore, the risk of tumor recurrence was higher in patients with residual tumor and in those who did not receive radiotherapy (13,14).…”
Section: █ Discussionmentioning
confidence: 94%
“…Moreover, postoperative recurrence rates were found to be significantly lower in patients who were asymptomatic than symptomatic at diagnosis of an incidentally detected NFPA (13). Furthermore, the risk of tumor recurrence was higher in patients with residual tumor and in those who did not receive radiotherapy (13,14). A meta-analysis also showed that lack of radiotherapy after initial pituitary surgery was associated with an increased risk of tumor recurrence surgery (18).…”
Section: █ Discussionmentioning
confidence: 96%
“…At this stage, more than 40% of NFPAs are invasive (3), so that complete surgical removal cannot be achieved. Reported recurrence rate varies between series, with up to 50% of patients experiencing long-term relapse (4,5). Management of patients with symptomatic residual and recurrent disease is challenging because no medical therapies are currently available.…”
Section: Introductionmentioning
confidence: 99%
“…An early diagnosis is obtained in the case of female patients [5] as reported by Nabarro [6]. The non-functioning pituitary adenomas are a heterogeneous subset of neoplasms of monoclonal origin of the adenohypophysis [7], which constitute 25-30% of pituitary neoplasias [8,9]. Diagnosis is usually established by detecting the predominant complications of neurological character, perhaps some degree of hypopituitarism, headache, and other clinical manifestations induced by the unpredictable biological behavior of those tumors.…”
Section: Introductionmentioning
confidence: 99%